Evaluering av et pedagogisk undervisningsopplegg i akademisk skriving - Eng, Anne-Lise; Løkkeberg, Stine Torp; Halvorsen , Lars Rune (Nordic Journal of Information Literacy in Higher Education, 2025)
At Østfold University College, we have focused on interdisciplinary collaboration to provide a comprehensive introduction to academic writing for first-year students, emphasizing a standardized program to ensure consistency in instruction. The article is divided into two studies. Both studies aimed to improve first-year students' academic writing skills by evaluating different instructional methods. The research questions for the studies were as follows: Study 1: Can the use of pre- and post-tests in an e-learning course in academic writing help students acquire new knowledge? Study 2: How do students experience blended teaching in academic writing? Study 1 examined whether pre- and post-tests in an e-learning course could help students acquire new knowledge in academic writing. An e-learning package was developed around eight themes: problem statement, text writing, sources, source criticism, study techniques, referencing techniques, plagiarism, and ethics. Forty-four first-year students took a pre-test of fifteen questions and received immediate feedback. After completing the instructional components for each theme, they took a post-test. Results showed significant improvement in post-tests, indicating increased understanding of the themes. Study 2 aimed to establish a quality-assured course package combining e-learning with on-campus instruction. A Facebook group was also created for students to ask questions about academic writing. Fifty-eight first-year students completed a questionnaire containing twelve different questions related to the evaluation of the various teaching methods in the blended instruction. In study 2, the evaluation of the academic writing course revealed that all three teaching methods were perceived as important for learning.